2013
DOI: 10.3109/21678421.2013.838586
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate repeat expansion length in C9orf72 may be pathological in amyotrophic lateral sclerosis

Abstract: An expanded hexanucleotide repeat in C9orf72 causes amyotrophic lateral sclerosis and frontotemporal dementia. All studies to date state that patients have a pathological expansion if they carry 30 or more repeats. We analysed the frequency of C9orf72 repeat expansions in a population based cohort of patients with ALS, and demonstrate that patients with between 20 and 30 repeats are phenotypically similar to patients with an expanded repeat length above 30 repeats. We propose that an intermediate repeat length… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 11 publications
0
31
1
1
Order By: Relevance
“…In other studies, a 29-repeat allele was found in a patient from a Dutch family with C9orf72-related FTD-ALS, 20 and four patients with limb-onset ALS with intermediate repeats (range 20-22) had lower mean (SD) age of diagnosis compared with patients with <20 repeats (47.6±15.9 vs 62.8±11.2 years). 9 Both patients in the latter study with 22 repeats exhibited cognitive and behavioural impairment similar to larger expansions and had family history of FTD, while two patients with 20 and 21 repeats had family history of dementia and psychiatric illness. In atypical PD or PD with psychosis, intermediate expansions (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) were detected in three female cases with atypical parkinsonian syndromes (severe rigid akinetic parkinsonism) and neuropsychiatric symptoms including schizoaffective psychosis and an FTD-like dementia.…”
Section: Original Articlementioning
confidence: 77%
See 1 more Smart Citation
“…In other studies, a 29-repeat allele was found in a patient from a Dutch family with C9orf72-related FTD-ALS, 20 and four patients with limb-onset ALS with intermediate repeats (range 20-22) had lower mean (SD) age of diagnosis compared with patients with <20 repeats (47.6±15.9 vs 62.8±11.2 years). 9 Both patients in the latter study with 22 repeats exhibited cognitive and behavioural impairment similar to larger expansions and had family history of FTD, while two patients with 20 and 21 repeats had family history of dementia and psychiatric illness. In atypical PD or PD with psychosis, intermediate expansions (20)(21)(22)(23)(24)(25)(26)(27)(28)(29) were detected in three female cases with atypical parkinsonian syndromes (severe rigid akinetic parkinsonism) and neuropsychiatric symptoms including schizoaffective psychosis and an FTD-like dementia.…”
Section: Original Articlementioning
confidence: 77%
“…51 In human kidney and neuroblastoma cell lines (HEK293T cells), intermediate repeats (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) have shown significantly decreased C9orf72 promoter activity compared with normal short repeats (2-6 units), 53 with lower transcriptional activity appearing more prominent in the presence of small deletions flanking the GGGGCC unit. Overall, these findings suggest that increasing repeat length can lead to decreased promoter activity via increased methylation of CpG sequences in larger repeats, with transcriptional silencing of the promoter.…”
Section: Intermediate Alleles Affect Normal Transcriptional Activity mentioning
confidence: 99%
“…Alleles in the intermediate range have prevalence rates of 0.3-0.6% among patients with ALS [85,93] and 0.3-4.6% among patients with FTD [85,90]. Some studies have suggested that intermediate-range alleles may increase the risk of disease because they segregate with disease [90], are a disease risk haplotype surrogate marker [1,29,69,90,94], and are associated with an early age of disease onset [93], decreased gene expression [29,71], and (in a zebrafish model) RNA foci toxicity [10].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that intermediate-range alleles may increase the risk of disease because they segregate with disease [90], are a disease risk haplotype surrogate marker [1,29,69,90,94], and are associated with an early age of disease onset [93], decreased gene expression [29,71], and (in a zebrafish model) RNA foci toxicity [10]. However, in a larger series, intermediate alleles were identified in control individuals [1,2,85] and were not associated with the age of onset or an increased disease risk for ALS [85], FTD [70,85], or ALS-FTD [85].…”
Section: Discussionmentioning
confidence: 99%
“…Healthy individuals generally carry no more than 20 repeats (and usually only a handful of such), but in persons with inherited FTLD or ALS, the expansion is huge, running to as many as 2,000 repeats [16,53]. Intermediate alleles of 20-30 repeats have been recorded [11,25], though the status of these in terms of disease risk remains unclear (see Cooper-Knock and Woollacott and Mead). Apart from questions as to how the expansion translates into disease mechanism, there are other serious issues to be resolved and explained.…”
mentioning
confidence: 99%